2007
DOI: 10.1016/j.cellimm.2007.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid promotes mouse splenic B cell surface IgG expression and maturation stimulated by CD40 and IL-4

Abstract: Retinoic acid (RA) increases antibody production in vivo but its role in B-cell activation is unclear. In a model of purified mouse splenic B cells stimulated by CD40 coreceptor (as a surrogate of T cell co-stimulation), IL-4, a principal Th-2 cytokine, and ligation of the B-cell antigen receptor, CD40 engagement or IL-4 alone induced B-cell activation indicated by increased Igγ1 germline transcripts, cell proliferation, and surface (s)IgG1 expression, while triple stimulation with the combination of anti-CD40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 60 publications
5
47
0
Order By: Relevance
“…Retinoic acid (RA), an active metabolite of vitamin A (ret-inol), is well known as a potent agent of cell differentiation, including for B cells (9,11,18,33,36) and other immunoregulatory cells. Vitamin A, RA, and related retinoids have been shown to be necessary for maintaining antigen-specific antibody responses (47).…”
mentioning
confidence: 99%
“…Retinoic acid (RA), an active metabolite of vitamin A (ret-inol), is well known as a potent agent of cell differentiation, including for B cells (9,11,18,33,36) and other immunoregulatory cells. Vitamin A, RA, and related retinoids have been shown to be necessary for maintaining antigen-specific antibody responses (47).…”
mentioning
confidence: 99%
“…The B cell proliferation and activation by up regulating co-receptor molecules is aided by similar molecules (Ma et al, 2005). Further, immunological diversity is controlled by RAR-ATRA receptor molecules by up regulating proteins needed for phenomena such as class switching and somatic hyper mutation (Cattoretti et al, 2006) while RAR-ATRA also helps in B cell maturation (Chen and Ross, 2007). In addition, RA paracrine signaling mechanisms allow cellular cross talking among leukocytes to overcome infectious conditions (Guo et al, 2015).…”
Section: Role Of Retinoic Acid In Immunitymentioning
confidence: 99%
“…Bone Morphogenic Proteins (BMP) which are under the Super family of Transforming Growth Factor β (TFG -β) are primarily responsible for carrying out molecular cross talking with other pathways which are essential for bone morphogenesis (Chen and Ross, 2007). Essential molecular communicating mechanism involves Smad1 protein and BMP proteins; which are prime molecules sustaining bone morphogenesis (Feng and Derynck, 2005;Wang et al, 2011).…”
Section: Maintenance Of Bones By Retinoic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that retinoic acid (RA) can enhance direct action on B cell populations [9]. RA can enhance antibody responses by a direct effect upon B cells, and modulate cytokine receptors to extend to B cells [23].…”
mentioning
confidence: 99%